THE BEHAVIOR OF T-SHAPED BUILDING STRUCTURES DUE TO DILATATION METHOD UNDER EARTHQUAKE LOADS - Nugroho, Febriansyah Ahmad; Budiman, Budiman; Hanif, Basit Al (International Journal of Civil Engineering and Infrastructure, 2024)
Earthquake resistant construction planning is very crucial in Indonesia, considering that most of Indonesia's territory is located in areas with moderate to high earthquake intensity. Especially the construction of high-rise buildings in the city of Jakarta which are built with irregular building plans. Therefore, development in the city of Jakarta must consider the earthquake forces that will occur on buildings to minimize losses caused by irregular building shapes. In this research, the irregularities of a T-shaped plan building will be planned, using a building split analysis method called dilatation, which will be modeled into 5 structural models, namely the first is a complete T-shaped plan or without dilatation, while the second and third models use the two-column dilatation method 1a and 1b, the fourth and fifth models use the cantilever dilatation method 1a and 1b. All models are designed with a special moment resisting frame system (SRPMK). This analysis aims to determine the earthquake force, structure period, and displacement of the structure. From the results of the structural analysis, the difference in the value of the structural period, the displacement between floors that occurs in dilated buildings, is obtained.